A Comparison of Acoustical Performance Between Traditional and Modern Church - Sai Kit, Phua; Che Din, Nazli (International Journal of Integrated Engineering, 2023)
Due to various worship approaches, churches’ plans and designs have evolved over time. In traditional churches, the chancel is where the preacher and choir are while the nave is where the audience is seated. The modern churches on the other hand usually follow the auditorium layout, where the chancel is replaced by a stage. The stage serves as a space for the musical worship and performances, other than preaching by the pastors. In acoustical terms, the chancel and the stage are known as the sound source and the audience is the sound receiver. It is essential to understand the relationship between the differences in the characteristics of traditional and modern churches and the impact on their acoustical performance. Two churches with different layout (cruciform and rectangular) from traditional and modern churches in Malaysia were selected to run a computer simulation using ODEON Room Acoustic Software. The results were then reviewed and analysed in acoustical parameters: (i) Reverberation Time (RT) and (ii) Speech Transmission Index (STI). Smaller church scored better in STI thus it is better for speech driven worship service as while bigger church scored better in RT thus it is more ideal for musical worship. In addition, the existing materials found in modern churches improved the overall acoustical performances. In conclusion, the church acoustical performance is affected by factors like the volume, distance between the sound origin, receivers and the surrounding walls, total absorption area and types of surface material and its absorption coefficient.